Red Ocean Strategy: Quadran Strategy in Building Bandung City Mosque Cooperative - Amaliah, Ima; Aspiranti, Tasya (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
The purpose of this study is how to optimize the problem solving of the Mosque Cooperative in Bandung City through the transformation of generic strategies and social innovation catalysts with the Red Ocean Management Strategy approach. Two steps have been taken, namely the identification of SWOT and the selection of generic strategies and social innovation catalysts through the Red Ocean Management Strategy approach. The results of the IFE and EFE SWOT analysis and are stated in the quadrant matrix identified in quadrant III, namely the mosque cooperative in a weak and threatened condition, where this condition is unfavorable for the mosque cooperative, which is dominated by the organization's internal weaknesses and threatened by the external environment. The Red Ocean strategy that must be carried out by mosque cooperative managers is focus and product differentiation by catalyzing innovation in the service process with priority on improving internal management.